Modern pollen rain in heathlands and adjacent forest phytocoenoses in Northern and Central Poland - Nienartowicz, Andrzej; Filbrandt-Czaja, Anna; Piernik, Agnieszka; Jabłoński, Piotr; Kunz, Mieczysław; Deptuła, Miłosz (Ecological Questions, 2013)
Differences between modern pollen rains in three types of phytocoenoses were studied in two regions, i.e. Tuchola Forest and Toruń Basin. The phytocoenoses in question were heaths, young pine-birch growths and mature pine tree stands, which form a temporal sequence and spatial mosaic in the landscape. In order to compare the structure of pollen samples, phytocoenoses and the landscape, the methods of numerical taxonomy were applied. An increase in the average number of sporomorphs was recorded, as well as in the taxonomic diversity of the pollen spectrum in this temporal sequence arranged from non-forest communities through young growths to mature forests. In the subsequent developmental stages, also the percentage contribution of Pinus pollen increased, as well as the total contribution of arboreal pollen (AP). The increase in the percentage contribution of arboreal pollen is accompanied by the decrease in the contribution of non-arboreal pollen (NAP), including Calluna and Ericaceae. Also a small increase in the number of species was observed. With the increased pine domination, however, the diversity of pollen types (expressed by rarefaction and Shannon-Wiener indices) decreases. As a result of the performed analyses, it was also found that the species composition of phytocoenoses and a pollen spectrum differs considerably, because the import of pollen from further areas exerts a significant influence on the structure of a palynological sample. The genus Calluna is the only type of plants characterized by a strong relationship between the occurrence in a phytocoenosis and in a surface pollen sample. Similarity between the taxa composition of a pollen spectrum and the landscape structure, consisting of a mosaic of phytocoenoses, seems to be higher than between a pollen sample and a phytocoenosis from which that sample was collected. The latter thesis, however, needs to be confirmed by further researches.